Effect of Hydrolyzed Bird’s Nest on β-Cell Function and Insulin Signaling in Type 2 Diabetic Mice - Choy, Ker Woon; Zain, Zuhaida Md; Murugan, Dharmani Devi; Giribabu, Nelli; Zamakshshari, Nor Hisam; Lim, Yang Mooi; Mustafa, Mohd Rais (Frontiers in Pharmacology, 2021)
Type 2 diabetes mellitus is characterized by both resistance to the action of insulin and defects in insulin secretion. Bird’s nest, which is derived from the saliva of swiftlets are well known to possess multiple health benefits dating back to Imperial China. However, it’s effect on diabetes mellitus and influence on the actions of insulin action remains to be investigated. In the present study, the effect of standardized aqueous extract of hydrolyzed edible bird nest (HBN) on metabolic characteristics and insulin signaling pathway in pancreas, liver and skeletal muscle of db/db, a type 2 diabetic mice model was investigated. Male db/db diabetic and its euglycemic control, C57BL/6J mice were administered HBN (75 and 150 mg/kg) or glibenclamide (1 mg/kg) orally for 28 days. Metabolic parameters were evaluated by measuring fasting blood glucose, serum insulin and oral glucose tolerance test (OGTT). Insulin signaling and activation of inflammatory pathways in liver, adipose, pancreas and muscle tissue were evaluated by Western blotting and immunohistochemistry. Pro-inflammatory cytokines were measured in the serum at the end of the treatment. The results showed that db/db mice treated with HBN significantly reversed the elevated fasting blood glucose, serum insulin, serum pro-inflammatory cytokines levels and the impaired OGTT without affecting the body weight of the mice in all groups. Furthermore, HBN treatment significantly ameliorated pathological changes and increased the protein expression of insulin, and glucose transporters in the pancreatic islets (GLUT-2), liver and skeletal muscle (GLUT-4). Likewise, the Western blots analysis denotes improved insulin signaling and antioxidant enzyme, decreased reactive oxygen species producing enzymes and inflammatory molecules in the liver and adipose tissues of HBN treated diabetic mice. These results suggest that HBN improves β-cell function and insulin signaling by attenuation of oxidative stress mediated chronic inflammation in the type 2 diabetic mice.